Expansion of the Meaning of Unlawful Acts in Corruption Cases: A Civil Law Perspective - Jupri Jupri; Alyas Alyas; Mala Ilyas; Umar. P; Muh. Syarif Lamanasa Lamanasa (Indonesian Civil Law Review, 2026)
This study aims to analyze the expansion of the meaning of unlawful acts in corruption cases from a civil law perspective as an alternative instrument for recovering state losses. The main issue addressed is the limitation of criminal law approaches, which have not been able to optimally restore state losses resulting from corruption. This research employs a normative legal method with statutory, conceptual, and case approaches, supported by primary, secondary, and tertiary legal materials. The findings indicate that the concept of unlawful acts can be expanded beyond violations of written legal norms to include breaches of public interest, propriety principles, and good governance. In this context, the state has legal standing as a subject of law to file civil lawsuits based on Article 1365 of the Civil Code against perpetrators of corruption and related parties. The novelty of this research lies in the integration model between criminal and civil law through civil litigation mechanisms, including the application of reversed burden of proof and the strengthening of asset recovery mechanisms. This approach is expected to create a more effective, comprehensive, and just anti-corruption system, particularly in recovering state losses.